Real production and real income growth over the COVID-19 pandemic - Sean Clarke; Ryan Macdonald (Economic and Social Reports)
The COVID-19 pandemic affected the Canadian economy in numerous ways, one of which was changing the relationship between growth in production, and changes in real consumption and real gross fixed capital formation (GFCF). Typically, real consumption and real GFCF are expected to progress similarly to real gross domestic product (GDP), however during the period covered by the COVID-19 pandemic, real consumption and real GFCF grew at a stronger pace than real GDP. This article illustrates how examining real income rather than real production can address this paradox. Specifically, the roles of changes in production (the use of capital, labour and multifactor productivity used to produce real GDP) and changes in non-production sources of real income growth (the trading gain and net income from abroad) are examined.